Improvement Teacher Skills in through Mentoring Virtual Reality Learning Media - Handayani, Trisni; Amirullah, Gufron; M. Jamil (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The industrial revolution era 4.0. technological developments in the world of education are increasingly rapid. Teachers as one of the determinants of the quality of graduate students are required to master technology for a smooth and innovative learning process. Millennial generation students are happy with the world of technology, one of which teachers can use to motivate students is to use virtual reality media. The development of making virtual reality-based learning media is one of the programs to improve teacher competence in teaching. The method used is the delivery of material by brainstorming then discussion and the latest games are problem-based solving and evaluation. This activity has a positive impact and provides new experiences for teachers to be implemented in the classroom because virtual reality engages several senses and memorable learning for students. So this training is needed by the teacher